The Role of Poetry in Promoting Social Values in Mesopotamia in the Twentieth Century - Yaseen, Asst. Prof. Dr. Sura Taha Yaseen (Sulaimani Journal for Humanities, 2026)
Literature, both poetry and prose, plays an important role in societies. It contributes to raising the awareness of individuals and their perception as a tool for spreading intellectual awareness and aesthetic values, and conveys a message to the recipient with specific goals. Since the Arabic poetry was the Arabs' record that chronicled their events, depicted their incidents and developments, and conveyed ideas, the social interest in it and its transmission among various circles was greater and broader than the interest in prose. This is the reason for our choice of poetry and talking about its role in strengthening social values after the renaissance whose features began after the formation of the new Iraq. To implement the research, a plan was developed consisting of an introduction and three chapters, at the end there is a conclusion, and the list of references. The first chapter will be about the political, economic and social conditions in Iraq, while the second chapter will be about poetry and social values - a quick historical overview - and the third chapter will be about the role of poetry in strengthening social values in Mesopotamia in the twentieth century. It is known that Mesopotamia was the richest country in poetry in the twentieth century. It is the country of Al-Jawahiri, Al-Habboubi, Bahr Al-Ulum, Al-Sayyab, Nazik Al-Malaika, and many others. At the end of the research comes the conclusion about the most important summary of what the research included, then a list of sources.
Keywords: Poetry; Social Values; Mesopotamia; Twentieth Century